Increased resistance of drought by Trichoderma harzianum fungal treatment correlates with increased secondary metabolites and proline content - Mona, S. Alwhibi; Hashem, Abeer; Abd_Allah, Elsayed Fathi; Alqarawi, Abdulaziz A.; Soliman, Dina Wafi K.; Wirth, Stephan; Egamberdieva, Dilfuza (Journal of Integrative Agriculture, 2017)
Plant secondary metabolites play vital role in plant stress response. In this study we investigated whether root colonization of tomato （Solanum lycopersicum） infected by Trichoderma harzianum leads to alterations in the biosynthesis of secondary plant metabolites including phytohormones and osmolyte proline under drought stress. Exposure of tomato to drought caused a drastic decline in plant growth and physiological parameters. Tomato inoculated with T. harzianum showed increased root and shoot growth and chlorophyll pigments as compared to uninoculated controls as well as drought stressed plants. Proline and total soluble protein content was increased in plants inoculated with T. harzianum under both normal as well as drought conditions. An obvious increase in phenol and flavonoid content was observed due to T. haczianum. In addition, T. hat-zianum inoculated plants maintained higher levels of growth regulators indole acetic acid, indole butyric acid, and gibberellic acid under drought stress. Improved secondary metabolites which play an important role in plant stress tolerance by T. hat-zianum may have coordinately worked for bringing the growth regulation by protecting membranes from reactive oxygen species （ROS） and enhance plant growth through accessing more nutrients by root system.